Noblewomen, aristocracy and power in the twelfth-century Anglo-Norman realm - Johns, Susan M. (Gender in history., 2003)
This is a study of noblewomen in 12th-century England and Normandy, and of the ways in which they exercised power. It offers a reconceptualization of women's role in aristocratic society, and in doing so suggests original ways of looking at lordship and the ruling elite in the high Middle Ages.